Automated Coding of Patient Discharge Summaries Using Conceptual Graphs - Delamarre, D.; Burgun, A.; Seka, L. P.; Le Beux, P. (Methods of Information in Medicine, 1995)
In medicine, as in other domains, indexing and classification is a natural human task which is used for information retrieval and representation. In the medical field, encoding of patient discharge summaries is still a manual time-consuming task. This paper describes an automated coding system of patient discharge summaries from the field of coronary diseases into the ICD-9-CM classification. The system is developed in the context of the European AIM MENELAS project, a natural-language understanding system which uses the conceptual-graph formalism. Indexing is performed by using a two-step processing scheme; a first recognition stage is implemented by a matching procedure and a secondary selection stage is made according to the coding priorities. We show the general features of the necessary translation of the classification terms in the conceptual-graph model, and for the coding rules compliance. An advantage of the system is to provide an objective evaluation and assessment procedure for natural-language understanding.
Keywords: Natural-Language Processing; Conceptual Graphs; Knowledge-Based System; Indexing; Coronary Diseases; ICD-9-CM